Beastly Boasts and Apocalyptic Affects: Reading Revelation in a Time of Trump and a Time of Plague - Moore, Stephen D. (Religions, 2020)
Waxing “biblical,” Donald Trump has described the COVID-19 pandemic as a “plague.” In a different but related register, millions of Christians worldwide have interpreted the pandemic as one of the eschatological plagues prophesied in the Book of Revelation. This article appropriates the reading tactics of Gilles Deleuze and Félix Guattari, together with the resources of affect theory, to connect the Book of Revelation with both the Trump phenomenon and the COVID-19 pandemic. Specifically, the article attempts to relate Revelation’s Beast to Trump (to unleash the Beast against Trump) non-eschatologically, in a non-representationalist reading strategy, and to analyze how Trump has manipulated the pandemic for his post-ideological ends.